The Causal Effects of R&D Grants: Evidence from a Regression Discontinuity - Santoleri, Pietro; Di Minin, Alberto; Martelli, Irene; Mina, Andrea (The Review of Economics and Statistics, 2024)
We leverage the discontinuity in the assignment mechanism of the Small and Medium Enterprise Instrument - the first European research and development (R&D) subsidy targeting small firms - to provide the broadest quasi-experimental evidence on R&D
Keywords: Quality Stamps; R and D Grants; Regression Discontinuity; Small and Medium Enterprises